The outcome of intracapsular hip fracture fixation using the Targon Femoral Neck (TFN) locking plate system or cannulated cancellous screws: A comparative study involving 2004 patients. Issue 11 (November 2017) - Alshameeri, Zeiad; Elbashir, Mohamed; Parker, Martyn J.
Abstract: Aim: This study compares the outcome of intracapsular hip fracture fixation using the Targon Femoral Neck (TFN) locking plate system with the standard fixation using cannulated cancellous screws (CCS). Patients and method: Analyses of a prospectively collected data of all patients treated for intracapsular hip fractures using the TFN system and CCS at our department over a period of 28 years. Baseline characteristics and specific outcome measures where compared. The primary outcome measure was fracture revision during the 1st year. Secondary outcome measures were fracture complications, any revision surgery, mortality and mobility status at one year after surgery. Results: A total of 2004 fractures were included, a third (n = 725, 36.2%) were treated using the TFN system. There were higher rates of non-union (19.5% vs 9.5%) and revision surgery (19% vs 9%) during the first year in the CCS cohort. Revision surgery was also higher in the same group during the whole of the follow-up period (22.2% vs 14.9%). The first year's mortality rate was higher in the CCS cohort (21.1% vs 17.5%) but the reduction in mobility and mobility scores was the same in both cohorts. Conclusion: This study includes the largest cohort of cases treated for intracapsular hip fractures using the TFN system. It demonstrated that the TFN system was associated with lower rates of non-union, revisions and re-operations for any cause.